Pengembangan E-Booklet Berbasis Aplikasi Android Pada Sub Konsep Sistem Peredaran Darah Manusia Kelas XI SMA - Norazijah, Sri Widiya Norazijah; Kaspul, Kaspul; Rezeki, Amalia (Yayasan Jompa Research and Development, 2024)
Electronic booklets are learning resources that are in accordance with online learning conditions, the 2013 curriculum and IT advances in education. The research model used is 4D namely: 1) Define, 2) Design and 3) Development which then in the Development stage uses the Tessmer Formative Evaluation design namely 1) Expert assessment and 2) individual test 3) small group test. The subjects of the validity test were 2 Biology Education lecturers and 1 Biology teacher at SMA Negeri 4 Banjarmasin. The individual test subjects were 3 class XI MIPA 3 students at SMA Negeri 4 Banjarmasin and the small group test subjects were 4 students in the same class. The results of the study show 1) the validity of the Android application-based E-Booklet based on 5 aspects has a valid category; 2) the practicality of the contents of the Android application-based E-Booklet has attractiveness based on the responses of students in the at least good category, the practicality of the hope that the E-Booklet is easy to use based on the responses of students in the least good category; and 3) the effectiveness of expectations based on critical thinking assessments obtains a very good category in interpretation, analysis, evaluation, explanation, and self-regulation skills, and has a good category in the aspect of inference